TRAINING AND MENTORING ON EARLY DETECTION AND TREATMENT OF CHILDHOOD GROWTH AND DEVELOPMENT DISORDERS IN ABA 05 KINDERGARTEN STUDENTS - Melizza, Nur; Dwi Kurnia, Anggraini; Masruroh, Nur Lailatul; Cahyanti, Aslamiyah; Kartika, Rika Yuni; Ayu Trisna, Indah; Rosalina, Casumi; Azlina, Qory (Universitas Airlangga, 2024)
Introduction: Early detection of growth and development is very important to be carried out to detect early deviations in growth and development in children. Independent monitoring of children's growth and development can be carried out by teaching staff at schools through various trainings in monitoring children's growth and development. This activity aims to provide training and assistance to students and teaching staff regarding the early detection and treatment of growth and development disorders so that if deviations are found, early intervention can be carried out so that growth and development return to normal or the deviations do not get worse. Methods: The methods used are counseling, training, demonstrations, and discussions carried out face-to-face. This activity was carried out at ABA 05 Kindergarten, Malang City by involving teachers (n=5) and students (n=52) in implementing the activity Results: The results obtained during the health examination were that 40% of students experienced dental caries and 2 students experienced growth and development disorders (speech delay). After being given training and assistance as well as practicing Early Detection of Child Growth and Development, participants were able to carry out early detection of child growth and development independently. Conclusion: This activity can be used as a good step to detect a child's growth and development so that appropriate intervention for growth and development disorders can be carried out as early as possible through collaboration between the school and parents.